Simplified joint-slippage model of bolted joint in lattice transmission tower. (August 2021) - Gan, Yi-de; Deng, Hong-zhou; Li, Chao
Abstract: Joint-slippage models are key parameters in structural deflection prediction of angle steel transmission towers. Depended by number of bolts, bolt diameter, bolt arrangement, cross section dimensions of angle steel and so on, there are so many different bolted joints with various joint-slippage characteristics in which only a few angle steel bolted joints were experimental tested. To determine the load-deformation relationship of bolted joints, a simplified joint-slippage model was proposed based on the component method. Then, the load-deformation relationship of two specimens of single-leg bolted joints and two specimens of lap-splice bolted joints were predicted by the proposed model and the finite element method in ABAQUS. Compared with the corresponding experimental results of other researchers, the validation of the proposed model and the finite element method were all verified. Furthermore, the load-deformation relationship of a single-leg bolted joint and a lap-splice bolted joint of a full-scale test tower were also predicted by the proposed model to further verify the validation of the model. Finally, structural deflection prediction of the test tower was conducted in ANSYS based on the proposed joint-slippage model. The predicted tower deflections were in good agreement with the test results.